2007
DOI: 10.1111/j.1365-2265.2007.03076.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of high‐risk patients with primary hyperparathyroidism – minimally invasive parathyroidectomy vs. medical treatment

Abstract: MIP can be safely performed under local anaesthesia and it facilitates clinical care in high-risk PHPT patients. It is recommended for those selected by image localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
13
0
3
Order By: Relevance
“…Our study finds that patients with crisis have similar incidence of MGD compared with non-crisis patients (6%). Other recent studies found that hypercalcemic crisis is likely to be caused by a single adenoma in 85%-92% of cases [2,4,11]. Furthermore, the current study shows that targeted parathyroidectomy without BNE can achieve excellent initial and long-term success rates with 0% mortality.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our study finds that patients with crisis have similar incidence of MGD compared with non-crisis patients (6%). Other recent studies found that hypercalcemic crisis is likely to be caused by a single adenoma in 85%-92% of cases [2,4,11]. Furthermore, the current study shows that targeted parathyroidectomy without BNE can achieve excellent initial and long-term success rates with 0% mortality.…”
Section: Discussionsupporting
confidence: 56%
“…Today, once biochemical evaluation confirms the diagnosis of hyperparathyroidism, imaging studies are performed to determine the location of the hypersecreting parathyroid adenoma. Over time, medical therapy followed by expeditious parathyroidectomy has been established as the treatment of choice in the treatment of patients with primary hyperparathyroidism presenting with hypercalcemic crisis [2][3][4][5][6][7][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Workshop guidelines state that imaging studies are not appropriate for confirming the diagnosis of PHPT or screening patients for surgical referral and that negative imaging findings should not preclude surgical referral or intervention. However, it is desirable to enforce the use of MIBI scintigraphy whenever possible because the localized diagnosis that can be achieved with this modality decreases the risk of surgical invasiveness, thereby increasing the operative success rate (19). The use of MIBI scintigraphy is advocated for determining whether surgery is indicated, even if the guideline criteria are not met.…”
Section: Discussionmentioning
confidence: 99%
“…Rubin et al (23) performed resection in 50 of 99 patients with asymptomatic PHPT and followed the subjects for a maximum of 15 years, reporting that the disease progressed in 37% of patients not treated surgically. Fang et al (19) performed resection in 19 of 33 PHPT patients with a high risk for surgery and provided medical treatment to 14 who refused surgery. The patients were followed for two to three years, with significant disease exacerbation observed in the non-surgically treated patients.…”
Section: Discussionmentioning
confidence: 99%